Financial Bookkeeping for Inmates of Class II B Women's Prison in Kupang - Makatita, Reyner; Fanggidae, Apriana; Kamuri, Klaasvakumok Jehezkielomi (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: The purpose of this activity is to provide knowledge about simple financial bookkeeping, enhance the skills of inmates in financial bookkeeping, understand effective financial management strategies, and encourage active participation of inmates in entrepreneurship upon their release. Method: The team determined the methods used in this activity, which are workshops, case studies, and practical exercises. Practical Applications: The outcomes of this activity include active participation of participants, indicating their interest and motivation to learn and enhance their knowledge in financial bookkeeping. Participants experience an increased understanding of financial management, especially in financial bookkeeping. They also develop improved practical skills in financial management, particularly in financial bookkeeping. Conclusion: This training has long-term impacts on participants. These impacts include increased financial independence, a change in perspective towards financial management, improved job skills, motivation to develop businesses after release, and minimizing the risk of reoffending.